Step-by-step explanation:
(2.6 X 10⁵)²
=6.76×10¹⁰
Multiply 7.22 onto 10b and -3
new equation - 72.2b-21.66=7b-14
add 21.66 onto -14
new equation - 72.2b=7b+7.66
subtract 7b from 72.2
new equation: 65.2b=7.66
divide 65.2 from b
new equation: b=7.66/65.2
final answer: b=0.117
Answer:
Step-by-step explanation:
A function is odd if f(-x) = -f(x)
A function is even if f(-x) = f(x)
And neither if neither are true.
In this case if we plugged in a negative x here
f(-x) = (-x)^3 - 11(-x)
f(-x) = -x^3 + 11
Therefore, this function is odd because if we pulled out a negative one again we would get back the original function. Or in other words f(-x) = -f(x) for f(x) = x^3 - 11x
Answer:
poop
Step-by-step explanation: